Efficacy of ecofriendly biocontrol Azotobacter chroococcum and Lac-tobacillus rhamnosus for enhancing plant growth and reducing infection by Neoscytalidium spp. in fig (Ficus carica L.) saplings - Alwan, Sabah Lateef; Hussein, Hawraa Neamah (Journal of Kerbala for Agricultural Sciences, 2019)
The aim of the research was to use the environment-friendly agents to reduce the effect of Neoscytalidium dimidiatum and Neoscytalidium novaehollandiae, that cause dieback and blacking stem on several agricultural crops. This disease was the first record on fig trees in Iraq by this study and registered in GenBank under accession numbers : MF682357 , MF682358, in addition to its involvement in causing dermatomycosis to human. In order to reduce environmental pollution due to chemical pesticides, two antagonistic bacteria Lactobacillus rhamnosus (isolated from yoghurt) and Azotobacter chroococcum (isolated from soil) were used to against pathogenic fungi N. dimidiatum and N. novahollandiae. The in vitro tests showed that both bio-agents bacteria were highly antagonistic to both pathogenic fungal reducing their radial growth to 44 and 75% respectively . Results of greenhouse experiments in pot showed that both A. chroococcum and L.rhamnosus decreased severity of infection by pathogenic fungi and enhanced plant health and growth. All the growth parameters of fig trees including leaf area, content of total chlorophyll, catalase and peroxidase activities were significantly higher compared to infected untreated control.